Diversity of Arbuscular Mycorrhizal Fungi In Palm Habitats of Pigafetta elata Lore Lindu National Park - Rinaldi malik; Yusran; Rukmi; Naharuddin; Henry Novero Barus; Rostiati Daeng Rahmatu; Rahmawati (Agricultural Science, 2026)
This study aimed to describe the species of arbuscular mycorrhizal fungi (AMF), analyze spore density, assess the level of AMF colonization in the roots of Pigafetta elata, and evaluate the physical and chemical properties of soils within its habitat.The study was conducted from August to October 2025. Soil and root samples of Pigafetta elata were collected from its habitats in Puroo Village, Lindu District, Sigi Regency, and Sedoa Village, North Lore District, Poso Regency. Soil samples were analyzed to identify AMF morphospecies and determine spore density, while root samples were analyzed to determine the percentage of root colonization. These analyses were carried out at the Forest Biotechnology Laboratory, Bogor Agricultural University (IPB University), Bogor, West Java. Analyses of soil physical and chemical properties were conducted at the Soil Science Laboratory, Faculty of Agriculture, Tadulako University, Palu.The results showed that in Puroo Village, three AMF morphospecies belonging to two genera (Acaulospora and Glomus) were identified, with a spore density of 5 spores per 20 g of soil and a root colonization rate of 49.56%. In contrast, in Sedoa Village, seventeen morphospecies belonging to three genera (Acaulospora, Glomus, and Gigaspora) were identified, with a spore density of 47 spores per 20 g of soil and a colonization rate of 45.84%. These differences were associated with edaphic conditions: Puroo had a near-neutral soil pH (6.30), high organic carbon content (4.15%), and good porosity (55.86%), whereas Sedoa had acidic soil conditions (pH 4.48), moderate organic carbon content (2.16%), and lower porosity (45.84%). This study revealed an ecological trade-off within AMF communities. In habitats with favorable soil conditions (Puroo), AMF allocated more energy to root colonization. Conversely, in environmentally stressed habitats (Sedoa), AMF produced a greater number of spores as a survival strategy. These findings provide baseline information for the conservation of Pigafetta elata and support the utilization of AMF as a biological agent in ecosystem restoration efforts